Investigation of the influence of the method of grape pomace processing before extraction on the organoleptic and physicochemical parameters of the extract - Yu. N. Chernyavskaya; A. A. Tyaguscheva; T. V. Pershakova (Новые технологии)
Introduction. Grape pomace is a by-product of the wine industry. It is a source of many biologically active substances with beneficial properties.The goal of the research was to study the dependence of organoleptic and physicochemical parameters of extracts from grape pomace of the Cabernet, Saperavi, Pervenets Magarach and Citronny Magarach varieties on the processing method (drying and freezing) of the pomace before extraction.The research methods included biochemical ones (acidity, content of polyphenolic substances, vitamin C, total and reducing sugars), commodity science methods (appearance, aroma, taste, color), mathematical analysis.The research results. It was found that the organoleptic assessment of extracts from pomace of red grape varieties was the highest for the frozen sample of the Cabernet variety (average score 4.0 versus 2.5-3.5 for the other samples); for white grape varieties, the organoleptic assessment of extracts did not differ fundamentally. The acidity of extracts from the pomace of red grape varieties (1.8-2.4%) was 3-9 times higher than that from the pomace of white varieties; at the same time, the acidity of extracts from frozen pomace was 0.3-0.6% higher. The highest content of polyphenolic substances was found in extracts from the pomace of the Saperavi variety (543.42 mg/100 g), the lowest – from that of the Citronny Magarach variety (179.68 mg/100 g); drying of the pomace led to a decrease in the polyphenol content by 30.37-44.70% depending on the variety. The content of vitamin C was in the range of 2.21-4.80 mg/100 g; drying led to a decrease in this indicator by 31.58-43.13% depending on the variety. The mass fraction of total sugars was in the range of 2.1- 6.3%, reducing sugars - in the range of 1.5-5.2% (in sweet pomace these indicators are 2 ... 3 times higher than in fermented ones); for three varieties out of four, drying led to a decrease in the mass fraction of sugars by 29.17-38.46%. The conclusion. The data obtained can be used in the development of a technology for the production of soft drinks using grape pomace as a source of biologically active substances.